Exploring Preschool Children’s Development of Writing in Brunei Darussalam - Siti Noorhanida Md Yussof (SEAMEO CECCEP, 2025)
This qualitative study explores the writing development of preschool children in Brunei Darussalam, a topic of growing interest given the nation's focus on literacy standards and the recognized importance of early literacy foundations. Six Bruneian preschool children aged five and six, categorized into three ability groups based on preschool literacy assessments, participated in the study. Data was collected using writing logs and semi-structured interviews. Findings indicate that all six children commenced their writing journeys at distinct developmental stages, irrespective of their assigned ability group. These diverse pathways in writing development were observed in high-ability children, middle-ability children, and low-ability children, revealing intriguing insights into their learning abilities and trajectories. This study contributes valuable insights to Brunei's focus on literacy standards, although it acknowledges the limitations of its small sample size and the potential benefits of future, larger-scale investigations, which would be able to draw more generalized conclusions.